1999
DOI: 10.1093/jn/129.3.602
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Inhibits Differentiation of Pre- and Post- Confluent 3T3-L1 Preadipocytes But Inhibits Cell Proliferation Only in Preconfluent Cells

Abstract: Conjugated linoleic acid (CLA; 18:2) is a group of isomers (mainly 9-cis, 11-trans and 10-trans, 12-cis) of linoleic acid. CLA is the product of rumen fermentation and can be found in the milk and muscle of ruminants. Animals fed CLA have a lower body fat content. The objective of this study was to establish the possible mechanisms by which CLA affects adipogenesis. 3T3-L1 is a well-established cell line that is used extensively in studying adipocyte biology. These cells typically grow in a culture medium unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(112 citation statements)
references
References 26 publications
11
95
0
6
Order By: Relevance
“…A novel finding of the present study is that treatment with oleic or linoleic acid, independent of insulin, was sufficient to induce lipid accumulation in 3T3-L1 cells. Many studies of adipocyte lineage cells report the addition of various hormone cocktails either with FCS (Brodie et al, 1999;Guo et al, 2000;Kang et al, 2003; or without FCS (Ding and Mersmann, 2001;Ding et al, 2002;Hsu and Ding, 2003;Hutley et al, 2003) in addition to FA to promote differentiation. These studies report that oleic and linoleic acids promote lipid accumulation in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel finding of the present study is that treatment with oleic or linoleic acid, independent of insulin, was sufficient to induce lipid accumulation in 3T3-L1 cells. Many studies of adipocyte lineage cells report the addition of various hormone cocktails either with FCS (Brodie et al, 1999;Guo et al, 2000;Kang et al, 2003; or without FCS (Ding and Mersmann, 2001;Ding et al, 2002;Hsu and Ding, 2003;Hutley et al, 2003) in addition to FA to promote differentiation. These studies report that oleic and linoleic acids promote lipid accumulation in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, octanoate appeared to attenuate differentiation in 3T3-L1 cells (Han et al, 2002). Conjugated linoleic acids have also been reported to inhibit differentiation in 3T3-L1 cells (Brodie et al, 1999;Kang et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…20,37,57 Consequently, several studies have demonstrated that CLA inhibits differentiation and represses adipocyte gene expression during the in vitro differentiation of mouse 3T3-L1 preadipocytes into adipocytes. 47,60,61 Owing to the differentiation of preadipocytes into adipocytes is an essential step to get mature adipocytes, which possess capability to take up, synthesize and store lipids, the inhibition on the differentiation of preadipocytes by CLA attributes to the observed lower triglyceride content and small adipocyte size.…”
Section: Cla Alters Preadipocyte Differentiationmentioning
confidence: 99%
“…Em outras palavras, a inibição da expressão desses genes resultaria na redução da lipogênese. Tal hipótese foi reforçada por Brodie et al 117 , Choi et al 118 , Takahashi et al 104 e Kang et al 109 , cujos trabalhos com culturas de pré-adipócitos 3T3-L1 e adipócitos humanos demonstram que o CLA inibe a ativação de fatores de transcrição que controlam a expressão de genes codificantes das proteínas C/EBPα, SCD e GLUT4, todas envolvidas no processo de diferenciação de celulas adiposas. Na verdade, os estudos apontam que a redução da gordura corporal induzida pelo CLA ocorre não somente pela diminuição do número de adipócitos, mas também, ou até mesmo somente, pela redução do seu tamanho.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified